Development of Hydroelectric Turbine Generator to Store Electrical Energy for Basic Home Appliance - Regyta Annafi Hidayat; Muhammad Asyraf Bin Zulkipli (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2024)
In response to the increasing demand for sustainable and decentralized energy solutions, the study investigates the integration of hydrokinetic power generation with effective energy storage systems Through meticulous engineering and technical innovation, the proposed system attempts to capture the renewable energy potential of flowing water, providing a stable supply of electricity for off-grid and remote households. A turbine derived from the overshot type used to transform the water distributed to the home, which has a significant flowrate, into kinetic energy. This kinetic energy is turned into electrical energy by a single-phase generator, data collected with time intervals and variable heads. The electrical energy produced by the generator is then stored in a battery for future use. Experimental results indicated varying efficiencies and charging durations for different water head levels. For instance, at a lower head level, the system required a longer charging duration. Increasing the head level led to improved efficiency and reduced charging times. These outcomes highlight the impact of water head variation on the performance of the hydroelectric turbine generator system. Higher head levels generally resulted in better efficiency and shorter charging times. Overall, the study provides insights into optimizing household-scale hydroelectric systems for sustainable electricity generation.